CODE-MIXING USED BY CINTA LAURA IN MATA NAJWA - Godefridus Bali Geroda; Rachel Yeusy (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2022)
The phenomenon of code-mixing has long attracted the interest of scholars who have investigated what triggers such events. Code mixing often occurs in a communication process. Some people tend to use English to replace or mix language codes in a communication process. It is necessary to get more information according to people familiar with English while speaking. This phenomenon helps us to feel comfortable with conversation and provides engagement with one another. This phenomenon will occur if the environment supports the use of bilingualism. The objectives of this research are to describe the type of code-mixing used by Cinta Laura in Mata Najwa and the reason why Cinta Laura used code-mixing in her utterance based on Hoffman's theory. This research uses a Qualitative Content Analysis Design. The result of the analysis shows that 37 data were code-mixing. These 35 data were insertion code-mixing. Another type is alternation code mixing there is 1 data and congruent lexicalization 1 data.